Metabolome responses of Enterococcus faecium to acid shock and nitrite stress. Issue 11 (23rd July 2020) - Yu, Zhong; Shi, Dongchen; Liu, Wencong; Meng, Yabing; Meng, Fangang
Abstract: Enterococcus faecium is gaining increasing interest due to its virulence and tolerance to a range of stresses (e.g., acid shock and nitrite stress in human stomach). The chemical taxonomy and basic structural features of cellular metabolite can provide us a deeper understanding of bacterial tolerance at molecular level. Here, we used hierarchical classification and molecular composition analysis to investigate the metabolome responses of E. faecium to acid shock and nitrite stress. Our results showed that considerable high biodegradable compounds (e.g., dipeptides) were produced by E. faecium under acid shock, while nitrite stress induced the accumulations of some low biodegradable compounds (e.g., organoheterocyclic compounds and benzenoids). Complete genome analysis and metabolic pathway profiling suggested that E. faecium produced high biodegradable metabolites responsible for the proton‐translocation and biofilm formation, which increase its tolerance to acid shock. Yet, the presence of low biodegradable metabolites due to the nitrite exposure could disturb the bacterial productions of surface proteins, and thus inhibiting biofilm formation. Our approach uncovered the hidden interactions between intracellular metabolites and exogenous stress, and will improve the understanding of host‐microbe interactions. Abstract : Global metabolomic responses of Enterococcus faecium to the hydrochloric acid shock and nitrite stress were mainly characterized through investigating the chemical taxonomy and biodegradability of metabolites. Here, the results showed that E. faecium produced considerable high biodegradable compounds under acid shock, while low biodegradable and nonutilizable compounds were accumulated in cell under nitrite stress. The difference in phenotype of E. faecium (e.g., biofilm formation) under two environmental conditions was further comparatively interpreted by the metabolite traits.